BS EN 1401-1 AMD 1. Plastics piping systems for non-pressure underground drainage and sewerage. Unplasticized poly(vinyl chloride) (PVC-U). Part 1. Specifications for pipes, fittings and the system (2nd June 2022) - British Standards Institution
No abstract available